2007
DOI: 10.1136/jcp.2005.029488
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating giant cellular blue naevus

Abstract: Introduction:Cellular blue naevi (CBN) measure 1–2 cm in diameter and affect the dermis, occasionally extending into the subcutaneous fat. The case of a 14-year-old boy with a giant CBN (GCBN) involving the right half of the face, the jugal mucosa and the lower eyelid with a tumour that had infiltrated the bone and the maxillary and ethmoidal sinuses is reported.Methods:Biopsies were taken from the skin, jugal mucosa and maxillary sinus. The following markers were used in the immunohistochemical evaluation: CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Malignant blue nevi (a type of melanoma) have been reported, especially within cellular blue nevi located on the scalp; in addition, cellular blue nevi may infiltrate deeply into local tissues in the absence of malignancy [85]. Although small, stable blue nevi require no intervention, lesions appearing suddenly or undergoing clinical change should be biopsied.…”
Section: Differential Diagnosis and Management Of Blue Nevimentioning
confidence: 99%
“…Malignant blue nevi (a type of melanoma) have been reported, especially within cellular blue nevi located on the scalp; in addition, cellular blue nevi may infiltrate deeply into local tissues in the absence of malignancy [85]. Although small, stable blue nevi require no intervention, lesions appearing suddenly or undergoing clinical change should be biopsied.…”
Section: Differential Diagnosis and Management Of Blue Nevimentioning
confidence: 99%
“…3 There are case reports describing CBN with respect to their anatomical location, size, and concern regarding malignant transformation. [3][4][5] Both the common and cellular blue nevi represent benign congenital entities within a spectrum of melanocytic tumours that contain dendritic and spindled melanocytes. Common blue nevi generally occur on the hands, feet, head, and neck region, whereas the cellular type has a propensity for the thigh and sacrococcygeal region.…”
Section: Discussionmentioning
confidence: 99%
“…4 These properties make PFCLs ideal substances to unfold and stabilize the retina, in addition to displacing subretinal fluid anteriorly. 5 PFCLs are used intraoperatively but are removed at the end of surgery to avoid inflammation mediated by toxicity that has been reported in animal and human studies. 6,7 We report a case of retained perfluoro-n-octane (PFO), a PFCL, and subsequent leakage into the orbit after its use for a retinal detachment in a globe with a perforating eye injury.…”
mentioning
confidence: 99%
“…The ''cellular'' BN (CBN), first described by Allen in 1949, usually appears on the skin of the buttocks, the head and neck and the extremities as a small melanocytic tumour of the dermis and subdermal tissue (Leopold and Richards, 1967). Clinical observations have shown that the CBN can become very large (Bittencourt et al, 2007) and infiltrate the subcutaneous soft tissue such as muscle, tendon or the bone of the scalp (Micali et al, 1997). Regional lymph node involvement (Misago et al, 2008) and the appearance of ''benign'' metastases to regional lymph nodes by a CBN are rare, but well documented (Bortolani et al, 1994;Gonzalez-Campora et al, 1994).…”
Section: Introductionmentioning
confidence: 99%